2012
DOI: 10.2147/copd.s31378
|View full text |Cite
|
Sign up to set email alerts
|

The importance of knowing the home conditions of patients receiving long-term oxygen therapy

Abstract: PurposeLong-term oxygen therapy (LTOT) is one of the main treatments for patients with chronic obstructive pulmonary disease. Patients receiving LTOT may have less than optimal home conditions and this may interfere with treatment. The objective of this study was, through home visits, to identify the characteristics of patients receiving LTOT and to develop knowledge regarding the home environments of these patients.MethodsNinety-seven patients with a mean age of 69 plus or minus 10.5 years were evaluated. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
10
1
7
Order By: Relevance
“…Cross-sectional studies have reported ‘added value’ from reviewing patients in their homes, which included identifying and correcting problems with the concentrator, humidifier, the length of the patient's tubing and factors impacting on the patient’s usage 56 57. In a prospective 10-year case–control study in which 217 LTOT patients were randomised to ‘home care’ (defined as 6-monthly hospital appointments and 2–3-monthly home visits) or standard care (management by hospital physician only), home care decreased exacerbation rates 58.…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…Cross-sectional studies have reported ‘added value’ from reviewing patients in their homes, which included identifying and correcting problems with the concentrator, humidifier, the length of the patient's tubing and factors impacting on the patient’s usage 56 57. In a prospective 10-year case–control study in which 217 LTOT patients were randomised to ‘home care’ (defined as 6-monthly hospital appointments and 2–3-monthly home visits) or standard care (management by hospital physician only), home care decreased exacerbation rates 58.…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…A small number of studies across a range of countries have used qualitative methods to explore the lived experience of people with COPD and their careers. Participants report physical limitations caused by their condition [9-11] causing reductions in meaningful activities [9,10,12,13] leading to reductions in social participation [9,12] and an increased feeling of dependency on their family and/or caregivers [14,15]. Depressive symptoms are also commonly reported [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Domiciliary oxygen therapy has become an important therapeutic measure in community-based rehabilitation for COPD patients (Godoy, Tanni, Hernandez, & Godoy, 2012). LTDOT is regarded as a therapeutic solution for COPD patients.…”
Section: Discussionmentioning
confidence: 99%